Radio Pakistan in the Digital Age - Sheikh, Muhammad Ahmad; Hassan, Ali Ab Ul; Tariq, Muhammad; Zia, Muhammad (Pakistan Journal of Humanities and Social Sciences, 2023)
With the advancement of technology, the use of streaming media by media petitioners has taken a quantum leap in recent years. The use of webcasting is now common in PSB (public sector broadcasting) across the globe. With the adaptation of the latest technology and its use in different program formats, Radio Pakistan has planned to use the best streaming gadgets in the coming years. Webcasting has increased the availability of radio communication, to anyone who has access to a computer. Pakistan Broadcasting Corporation, commonly known as Radio Pakistan, adopted web-based technology for its programming in 2010 in its initial stages. To reach across the globe, medium waves and FM broadcasts of Radio Pakistan are now using Garden Radio Apps to increase their listenership and improve their reception. Under the vision, ‘’Digital Pakistan had decided on a complete digital migration of Radio Pakistan under the Phase 1 and Phase 11 DRM (Digital Radio Mondiale) Plan.